Patients' experience of shoulder disorders: a systematic review of qualitative studies for the OMERACT Shoulder Core Domain Set - Page, Matthew J; O'Connor, Denise A; Malek, Mary; Haas, Romi; Beaton, Dorcas; Huang, Hsiaomin; Ramiro, Sofia; Richards, Pamela; Voshaar, Marieke J H; Shea, Beverley; Verhagen, Arianne P; Whittle, Samuel L; et al. (Rheumatology (Oxford, England), 2019)
To describe the experiences (including symptoms and perceived impacts on daily living) of people with a shoulder disorder. Systematic review of qualitative studies. We searched for eligible qualitative studies indexed in Ovid MEDLINE, Ovid Embase, CINAHL (EBSCO), SportDiscus (EBSCO) and Ovid PsycINFO up until November 2017. Two authors independently screened studies for inclusion, appraised their methodological quality using the Critical Appraisal Skills Programme checklist, used thematic synthesis methods to generate themes describing the experiences reported by participants and assessed the confidence in the findings using the Grading of Recommendations Assessment, Development and Evaluation Confidence in Evidence from Reviews of Qualitative research (GRADE-CERQual) approach. The inclusion criteria were met by eight studies, which included 133 participants (49 females and 84 males) with either rotator cuff disease, adhesive capsulitis, proximal humeral fracture, shoulder instability or unspecified shoulder pain. We generated seven themes to describe what people in the included studies reported experiencing: pain; physical function/activity limitations; participation restriction; sleep disruption; cognitive dysfunction; emotional distress; and other pathophysiological manifestations (other than pain). There were interactions between the themes, with particular experiences impacting on others (e.g. pain leading to reduced activities and sleep disruption). Following grading of the evidence, we considered it likely that most of the review findings were a reasonable representation of the experiences of people with shoulder disorders. Patients with shoulder disorders contend with considerable disruption to their life. The experiences described should be considered by researchers seeking to select the most appropriate outcomes to measure in clinical trials and other research studies in people with shoulder disorders.